Representasi Fanatisme Suporter terhadap Tim Sepak Bola dalam Film Dokumenter - Ilham Akbar Mutaqin; Mochamad Rochim (UNISBA Press, 2023)
Abstract. Basically, football and supporters are an inseparable unit. Football without fans is like vegetables without salt, it's tasteless. The fanatic attitude of the fans for their favorite team is often used as a plot in a film. Ranging from fiction films to documentaries that depict real life events, as well as facts that occur in real life. As in the documentary Stay True To Your Legacy: Persib Blody Hell (Viking the Conqueror) which is a documentary about the story of supporters of one of the Pesib Bandung football clubs made by the YouTube channel Beutik Company. This documentary tells the story of how the Vikings supporter group loves and loves the football club Persib Bandung. The purpose of this study was to find out how the representation of fanaticism of fans towards football clubs in the documentary film Stay True To Your Legacy: Persib Blody Hell (Viking Sang Penakluk). The method used in this study is a qualitative method with an analysis of the semiotic approach of Roland Barthes. The results of this study are concluded as follows: 1. The denotative meaning is that the Viking Persib Club supporter group often shows fanaticism in the form of their support for the Persib Bandung football team, 2. The connotative meaning is that there are several scenes that have the meaning of fanaticism from the Viking Persib supporters group. Club when they supported the Persib Bandung team. One of them is that some members of the Viking Persib Club supporter group when they don't have money to buy match tickets, they are willing to pawn and sell their personal belongings in order to buy Persib match tickets, 3. The meaning of the myth is that there are several scenes that represent the fanaticism shown by the Viking supporters group. Persib Club when they supported the football team Persib Bandung. There are many scenes whose mythological meanings are almost the same as each other, one example is the fanatical attitude of the Viking Persib Club supporters group causing them to be unable to think rationally. There is a scene that shows that members of the Viking supporter group are willing to clash with the supporters team Abstrak. Pada dasarnya, memang sepak bola dan suporter merupakan satu kesatuan yang sulit untuk dipisahkan. Sepak bola tanpa adanya suporter seperti sayur tanpa garam, hambar rasanya. Sikap fanatik para penggemar terhadap tim kesayangannya kerap dijadikan sebagai plot dalam suatu film. Dari mulai dari film fiksi hingga dokumenter yang menggambarkan peristiwa kehidupan nyata, serta pula fakta yang terjadi dalam kehidupan nyata. Seperti pada film dokumenter Stay True To Your Legacy : Persib Blody Hell (Viking Sang Penakluk) yang merupakan sebuah film dokumenter mengenai kisah suporter dari salah satu klub sepak bola Pesib Bandung yang dibuat oleh channel YouTube Beutik Company. Film dokumenter ini mengisahkan bagaimana kelompok suporter Viking dalam mendukung serta mencintai klub sepak bola Persib Bandung. Tujuan penelitian ini yaitu untuk mengetahui bagaimana representasi fanatisme suporter terhadap klub sepak bola dalam film dokumenter Stay True To Your Legacy : Persib Blody Hell (Viking Sang Penakluk). Metode yang digunakan dalam penelitian ini yaitu metode kualitatif dengan pendekatan analisis semiotika roland barthes. Hasil pada penelitian ini disimpulkan dengan berikut : 1. makna denotasi yaitu kelompok suporter Viking Persib Club kerap kali memperlihatkan fanatisme dalam bentuk dukungan mereka kepada tim sepak bola Persib Bandung, 2. Makna konotasinya adalah terdapat beberapa adegan yang memiliki makna fanatisme dari kelompok suporter Viking Persib Club ketika mereka mendukung tim Persib Bandung. Salah satunya adalah beberapa anggota kelompok suporter Viking Persib Club ketika tidak memiliki uang untuk membeli tiket pertandingan, mereka rela menggadai hingga menjual barang pribadi mereka agar bisa membeli tiket pertandingan Persib, 3. Makna mitos terdapat beberapa adegan yang mempresentasikan fanatisme yang ditunjukan oleh kelompok suporter Viking Persib Club ketika mereka mendukung tim sepak bola Persib Bandung.